Spontaneously painful piezogenic pedal papules in Ehlers-Danlos syndrome. - Cutrone, M. (European Journal of Pediatric Dermatology, 2007)
Plantar piezogenic papules are not exceptional in the obese child, due to herniation of the fat tissue into the reticular dermis and thus are not a warning sign. They can be painful only due to prolonged and excessive pression. On the other hand, when spontaneously painful, the pedal piezogenic papules can be a typical sign of Ehlers-Danlos syndrome.